Analisis Kendala dalam Pembelajaran Bangun Datar di Sekolah Dasar : Tantangan bagi Guru dan Siswa - Jennie Jevera Nathaniela Almi; Mohammad Dwiyan Ramadhan; Kowiyah Kowiyah (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to analyze the obstacles faced in learning flat shapes in elementary schools, both by teachers and students. The research method used is descriptive qualitative through observation and interviews with teachers in elementary schools. The research results show that the main obstacles faced by teachers are limited interactive learning media and limited time to practice the material in depth. Meanwhile, obstacles for students are difficulties in understanding abstract concepts and lack of interest in mathematical material. Based on the results of the analysis, this research suggests using more varied learning media and developing more interactive teaching strategies to increase students' understanding and interest in learning flat figures.